Cuproptosis-related modification patterns depict the tumor microenvironment, precision immunotherapy, and prognosis of kidney renal clear cell carcinoma - Cai, Zhiyong; He, You'e; Yu, Zhengzheng; Hu, Jiao; Xiao, Zicheng; Zu, Xiongbing; Li, Zhenghao; Li, Huihuang (Frontiers in Immunology, 2022)
Background: Due to different infiltration abundance of immune cells in tumor, the efficacy of immunotherapy varies widely among individuals. Recently, growing evidence suggested that cuproptosis has impact on cancer immunity profoundly. However, the roles of cuproptosis in tumor microenvironment (TME) and in response to immunotherapy are still unclear. Methods: Unsupervised clustering was employed to identify cuproptosis-based patterns in kidney renal clear cell carcinoma (KIRC). Cuproptosis signature was constructed by ssGSEA algorithm for personalized evaluating infiltration of leukocytes and efficacy of immune checkpoint blockade (ICB) in KIRC. Cuproptosis risk score was built by random forest model for customized estimating survival probability of individual. Results: Two distinct cuproptosis-based patterns were developed. Cluster 1 showed better prognosis, more active immune-related pathways and higher infiltrating level of immune cells than Cluster 2. Additionally, cuproptosis signature not only could be used for conducting individual assessment on cancer immunity steps and infiltration abundance of leukocytes, but also for evaluating individual’s sensitivity to ICB. Patients with high-score of cuproptosis signature exhibited more activated cancer immune process, higher inflammatory infiltration level in TME and better curative efficacy of ICB in comparison with low-score patient. Further, a robust cuproptosis risk score indicated that high-risk individuals showed worse survival outcomes than low-risk individuals. Ultimately, a nomogram combined the risk score with prognostic clinical factors was developed and showed excellent prediction accuracy for overall survival (OS). Conclusion: Distinct cuproptosis-related patterns in KIRC have significant differences on prognosis and immune-related pathways. Cuproptosis signature and cuproptosis risk score are able to provide guidance for precision therapy and predict prognosis for patient with KIRC in clinical practice.